An Assesment of the Impact of New Technologies on the right to Freedom of Expression in Uganda - John Zake Senoga Kagutema (Uganda Christian University, 2025)
Because of the rapid development in technology, the right to freedom of expression in Uganda is in question, this research aims at providing a comprehensive analysis of laws and regulations in conjunction with technology from Uganda’s perspective. It will explore the various approaches adopted by Uganda, highlighting key legislative instruments, regulatory bodies, and enforcement mechanisms. Using a quantitative research methodology, this research will examine the challenges met in implementing the laws on cyber security in Uganda and also analyses the laws such as the Computer Misuse Act, 2011; (2) Electronic Transactions Act, 2011; and (3) Electronic Signatures Act, 2011. Ultimately, this research underscores the importance of international cooperation and dialogue in addressing the complex and evolving landscape of cyber security threats. As cyber risks continue to evolve, so too must the legal frameworks designed to mitigate them, ensuring that they are both effective and adaptable to the changing dynamics of the digital age. It should be equally noted that today a great part of life is based on digital connectivity and digital transformation is reshaping industries and societies, the protection of data and critical infrastructure from cyber threats has become a paramount concern. Cyber security incidents, ranging from data breaches to ransom ware attacks, have escalated in frequency and sophistication, underscoring the vulnerabilities inherent in our interconnected world. Governments, businesses, and individuals are increasingly recognizing the need for robust cyber security measures to safeguard sensitive information, protect privacy, and ensure the continuity of essential services.